Nivel de conocimiento sobre enfermedades Diarreicas Agudas y su relación con las prácticas de las madres, en niños menores de 5 años atendidos en el Centro de Salud 9 De Abril, Tarapoto, Abril – Octubre 2016 - Tejada Tavera, Carolina (2017)
The following reserch was aimed to detemine the level of knowledge and its relation with the practtces of acute diarrheal diseases in mothers of Children under the age of 5 years attended at the "9 de Abril" Health Center, Tarapoto, April _ October, 2016. This was a quantitative, descriptive, prospective, cross - sectional study, with a correlational design. The sample was represented by 77 mothers of children under ages of 5 years. The technique used was a questionnaire with 31 questions. Results: 57.2% of the mothers are older than 26 years old, 42.9% have incomplete secondary studies, 72.7% are housewives and 75.3% are living partners. 40.3% of mothers have a sufficient level of knowledge about ADDs. 54.5% have preventative practices and management of inadequate ADDs. 90% do not prepare foods with fresh supplies, 57.5% do not put garbage deposits away from home, and 47.5% do not wash their hands with soap before and after food preparing, changing diapers, going to the bathroom, eating foods. 19% of them do not provide exclusive breastfeeding, 55% continue with normal feeding when the child has diarrhea, 65% feed their child 4 times a day, and 97.5% do not know how to prepare homemade whey and 62.5 o/o does not use oral rehydration salts. Conclusion: There is a statistically significant relationship between the levels of knowledge and the preventiva practicas and management of the ADDs in mothers of chiilldren under ages of 5 years (p <0.05)